Educação Popular e Educação do Campo: análise a partir do Programa Nacional de Educação da Reforma Agrária no curso Pedagogia da Terra em São Carlos - SP - Rossi, Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Education is not disconnected from other social complex, their autonomy is relative and its dependence is ontological nature with work, understood as a basic category of social being. In this sense, this thesis establishes a reflection on Field Education in the midst of class struggle present in the Brazilian agrarian question both with regard to the territorial disputes between classes with opposing and irreconcilable interests, as with regard to educational projects that arise from different divergent school teaching proposed in the field. With this horizon analysis we treated in Chapter 01 State discussion and determination of class beyond the positions that consider it neutral or impartial in the face of social inequalities and advance the understanding of the history of Brazilian agrarian question until the consolidation dominant agribusiness and its contradictions in contemporary times. As continuity, we discuss in Chapter 02 the discussion of popular education as an educational strategy of struggle and resistance of several workers, understanding their challenges facing the challenge of human emancipation and, therefore, the education field in their historical trajectories of conquests and confrontations. In chapter 03 we treat the territorial disputes between peasants and agribusiness differentiating education from field of education rural or to field in an effort to understand the ideology as a constituent element of such struggles...

A Educação não está desvinculada dos demais complexos sociais, sua autonomia é relativa e sua dependência é de cunho ontológico com o trabalho entendido enquanto categoria fundante do ser social. Nesse sentido, a presente tese estabelece uma reflexão a respeito da Educação do Campo em meio às lutas de classe presentes na questão agrária brasileira tanto no que se refere às disputas territoriais entre classes com interesses opostos e inconciliáveis, quanto no que diz respeito aos projetos educacionais que se manifestam a partir de diferentes e divergentes propostas pedagógicas em escolas no campo. Com esse horizonte de análise tratamos no capítulo 01 a discussão do Estado e sua determinação de classe para além das posturas que o consideram como ―neutro‖ ou ―imparcial‖ frente às desigualdades sociais e avançamos no entendimento da história da questão agrária brasileira até a consolidação dominante do agronegócio e suas contradições na contemporaneidade. Como continuidade, abordamos no capítulo 02 a discussão de educação popular enquanto estratégia educativa de luta e resistência de diversos trabalhadores, entendendo seus desafios frente ao desafio da emancipação humana e, com isso, a educação do campo em suas trajetórias históricas de conquistas e enfrentamentos. No capítulo 03 tratamos das disputas territoriais entre o campesinato e o agronegócio diferenciando a educação ―do‖ campo da educação ―rural‖ ou ―para‖ o campo, num esforço de compreender a ideologia enquanto elemento constituinte de tais lutas...
Keywords: Educação; Educação do campo; Agricultura e Estado; Education